2016
DOI: 10.18632/oncotarget.14369
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal microRNAs as prognostic biomarkers for non-small-cell lung cancer

Abstract: Exosomal miRNAs are proposed as excellent candidate biomarkers for clinical applications. However, little is known about their potential roles as prognostic biomarkers in lung cancer. In this study, we explored the prognostic value of plasma exosomal microRNAs (miRNAs) for non-small-cell lung cancer (NSCLC). Using a quantitative polymerase chain reaction (qPCR) array panel, we analyzed 84 plasma exosomal miRNAs in 10 lung adenocarcinoma patients and 10 matched healthy controls. The qPCR array showed 30 aberran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
155
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(162 citation statements)
references
References 67 publications
3
155
0
4
Order By: Relevance
“…Elevated levels of exosomal miR-23b-3p, miR-10b-5p and miR-21-5p were independently associated with poor OS [with hazard ratio of 2.42 (1.45-4.04), P=0.001; 2.22 (1.18-4.16), P=0.013; 2.12 (1.28-3.49), P=0.003, respectively]. When compared to a model derived from clinical prognostic variables, adding the three exosomal miRNA signatures significantly improved survival predictive accuracy with an increase of timedependent area under the receiver operating characteristic curve from 0.88 to 0.91 (P=0.015) (26).…”
Section: Micrornas (Mirs)mentioning
confidence: 94%
See 1 more Smart Citation
“…Elevated levels of exosomal miR-23b-3p, miR-10b-5p and miR-21-5p were independently associated with poor OS [with hazard ratio of 2.42 (1.45-4.04), P=0.001; 2.22 (1.18-4.16), P=0.013; 2.12 (1.28-3.49), P=0.003, respectively]. When compared to a model derived from clinical prognostic variables, adding the three exosomal miRNA signatures significantly improved survival predictive accuracy with an increase of timedependent area under the receiver operating characteristic curve from 0.88 to 0.91 (P=0.015) (26).…”
Section: Micrornas (Mirs)mentioning
confidence: 94%
“…Moreover, RNA, including miRs are much more stable when isolated and stored together with exosomes, providing higher yield. In a recent study (26), with a quantitative polymerase chain reaction (qPCR) array panel, 84 plasma exosomal miR samples were analyzed from 10 patients with NSCLC and 10 healthy controls. Elevated levels of exosomal miR-23b-3p, miR-10b-5p and miR-21-5p were independently associated with poor OS [with hazard ratio of 2.42 (1.45-4.04), P=0.001; 2.22 (1.18-4.16), P=0.013; 2.12 (1.28-3.49), P=0.003, respectively].…”
Section: Micrornas (Mirs)mentioning
confidence: 99%
“…Recently, exosomal transport of miRNAs has gained attention as a carrier of genetic information [18]. Regarding NSCLC patients, only a few papers have reported on the usefulness of exosomal miRNA as a prognostic biomarker [19][20][21]. It was shown that miR-146a-5p levels in serum exosomes predict progression-free survival of NSCLC patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that miR-146a-5p levels in serum exosomes predict progression-free survival of NSCLC patients [19]. Another study reported that elevated levels of plasma exosomal miR-23b-3p, miR-10b-5p, and miR-21-5p were prognostic biomarkers for NSCLC patients [20]. Our group also demonstrated that miR-21 and miR-4257 levels of plasma exosomes are useful biomarkers for diseasefree survival (DFS) of NSCLC patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…Liu and colleagues used a quantitative polymerase chain reaction (qPCR) array panel to analyze 84 plasma exosomal miRNAs in 10 lung adenocarcinoma patients and 10 matched healthy controls. The results showed that increased levels of exosomal miR-23b-3p, miR-10b-5p and miR-21-5p were independently related to poor overall survival [27]. Rabinowits et al evaluated the expression levels of specific exosomal miRNAs in patients with and without lung adenocarcinoma and they though circulating exosomal miRNA might be useful as an acceptable marker for diagnosis and prognosis in patients with lung cancer [28].…”
Section: Exosomal Mirnas As Diagnostic and Predictive Biomarkers In Lmentioning
confidence: 99%